Application of wireless monitoring and communication systems in the power engineering - Grechikhin, V.A.; Zamolodchikov, V.N.; Smolskiy, S.M. (Технология и конструирование в электронной аппаратуре, 2012)
The article describes some achievements of modern radio electronics, which prove a huge potential of modem wireless engineering for using in the fuel-energy complex. Wireless corporation communication systems, application of short-range radar measuring systems on the power engineering objects, prospects of laser measuring systems, methods of radio thermography and radio spectroscopy, wireless acoustic-electronic sensors are discussed. Описаны некоторые достижения современной радиоэлектроники, которые свидетельствуют о громадном потенциале современной беспроводной техники и достижений радиоэлектроники для использования в топливно-энергетическом комплексе. Рассмотрены беспроводные корпоративные системы связи, вопросы применения на энергетических объектах измерительных систем ближней радиолокации, перспективы использования лазерных измерительных систем, методы радиотермографии и радиоспектроскопии, возможности беспроводных акустоэлектроных датчиков. Описано деякі досягнення сучасної радіоелектроніки, які свідчать про величезний потенціал сучасної бездротової техніки та досягнень радіоелектроніки для використання у паливно-енергетичному комплексі. Розглянуто бездротові корпоративні системи зв'язку, питання застосування на енергетичних об'єктах вимірювальних систем ближньої радіолокації, перспективи використання лазерних вимірювальних систем, методи радіотермографії та радіоспектроскопії, можливості бездротових акустоелектронних датчиків.